PROSPECTS OF UKRAINE LOW-COST AVIATION - Kasianova, Nataliia; Suvorova, Kateryna (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose of the article is to show that the budgetary development of aviation in the market of domestic flights in Ukraine will not only increase the use of the aircraft by the end user, but also maximize the profits for the domestic airlines. Methods: We used economic analysis methods to assess the costs for air travel. The necessity of the use of passengers load factor was justified, indicators of the efficiency of the airline were calculated. The advantages of the air transport compared to the rail transport were shown on the basis of a comparative analysis. Results: We considered the relationship between the volume of air traffic and the revenue of the potential clients. The feasibility of reducing prices on air tickets to the level of railway tariffs was proved. The concept of low cost airlines was defined, the factors to decrease the air travel prices were identified. Maximisation of the airline profits can be achieved with an affordable price, which will increase passenger traffic. Discussion: In Ukraine there is an urgent need for new solutions that would help airlines to successfully conduct its business and meet the needs of passengers on domestic routes. There is no doubt that in times of economic crisis, inflation has a significant impact on the real incomes of consumers, and this study proves the feasibility of establishing a low-budget domestic aviation and its use on domestic routes during the economic crisis.